Comparing the effect of a simulated defender and dual-task on lower limb coordination and variability during a side-cut in basketball players with and without anterior cruciate ligament injury - Heidarnia, E.; Letafatkar, A.; Khaleghi-Tazji, M.; Grooms, D. R. (Journal of Biomechanics, 2022)
Anterior Cruciate Ligament (ACL) injuries commonly occur when attention is simultaneously on the environment (other players, objects) and maintaining neuromuscular control. Therefore, our purpose was to investigate lower-extremity coordination following ACLR during a run-to-cut with ecological validity to sport competition. Sixteen male basketball players with ACLR (20.8 ± 3.42 years, time since surgery: 9.5 ± 2.4 months) were contrasted with 16 healthy male control basketball players (21.3 ± 3.17 years) during a run-to-cut maneuver under two conditions: 1) standard, run and initiate a ~40° side-cut and 2) simulated sport, run-to-cut with the presence of a defender and engaged in a dual-task to intercept a ball. Lower limb kinematics were used to calculate continuous relative phase metrics for evaluation of coordination pattern and variability. Independent t-test and effect size were used to evaluate the difference between the two groups and across condition via change score. The simulated sports cutting maneuver coordination patterns were significantly different between groups for hip-ankle, hip-knee, knee-knee, and knee-ankle coupling (p < .05). Only hip-knee coupling had a significant condition change score (p = .01) with ACLR increasing (51.8 ± 79.1%) and healthy controls (-16.04 ± 64.1%) decreasing hip flexion-extension and keen abduction-adduction coupling. There was no significant difference in normal cut coordination between groups. The addition of simulated sport visual attention and dual task motor planning during the run-to-cut might elicit different lower limb movement patterns in ACLR athletes compared to the healthy counterparts, potentially contributing to the elevated reinjury risk in those with ACLR history when returning to sport.